Casino Paradise: The Turkish Cypriots and Gambling Addiction - Macit, Ruken (Addicta: The Turkish Journal on Addictions, 2020)
Cyprus, which is surrounded by Turkey in the north, Syria in the east, Israel, Palestine, and Lebanon in the southeast, and Egypt in the south, is the third-largest island in the Mediterranean. The island has been divided into two separate states, i.e., the Turkish Republic of Northern Cyprus (TRNC) and the Republic of Cyprus (Cyprus), since military action by Turkey in 1974. However, the TRNC is recognized by no country other than Turkey and has been blockaded politically, socially, and economically. As a result, it has become a casino paradise that harbors all kinds of illegal activities. In this study, semistructured interviews were conducted with 20 gamblers and one casino manager living in Cyprus. The social life experienced in a situation of political isolation and the effect of this situation on an individual’s gambling habits were analyzed. A positive relationship was identified between the political situation of Northern Cyprus since 1974 and Turkish Cypriots’ gambling addiction. The findings indicate that social, economic, and political arrangements should be made in accordance with the political situation of Northern Cyprus.